afla termenul necunoscut {[(a-2)÷3-1]÷2-1}÷2=1
Răspunsuri la întrebare
Răspuns de
0
[(a-2):3-1]:2-1=1•2
[(a-2):3-1]:2-1=2
[(a-2):3-1]:2=1+2
[(a-2):3-1]:2=3
(a-2):3-1=3•2
(a-2):3-1=6
(a-2):3=6+1
(a-2):3=7
a-2=7•3
a-2=21
a=21+2
a=23
[(a-2):3-1]:2-1=2
[(a-2):3-1]:2=1+2
[(a-2):3-1]:2=3
(a-2):3-1=3•2
(a-2):3-1=6
(a-2):3=6+1
(a-2):3=7
a-2=7•3
a-2=21
a=21+2
a=23
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Geografie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă